MODELING ANALYSIS OF A SPATIAL 3T CABLE-DRIVEN PARALLEL ROBOT - CUI Hai; SHEN BoKan (Jixie qiangdu)
A spatial 3T cable-driven parallel robot with four cables has been designed and manufactured. The kinematic models of the 3DOF cable-driven parallel robot have been established to discuss the deformation of cables in the large scale system. To check for the system’s zero position and analysis the error,the forward solution of kinematics has been carried out by Newton-Raphson iterative method. After analyzing the distribution of the dexterity,target tracks have been planned in the work space. Based on the inverse kinematics,the ideal curves of cables’ length have been reached. Based on catenary theory,the change of cables’ length have been calculated which is caused by the transformation,the result provide the theory basis for subsequent control.